Efektivitas Pembelajaran Berbasis Game dalam Meningkatkan Minat Belajar Matematika di MI Negeri 36 Aceh Besar - Nurlaili, Nurlaili; Nurjihan, Nurjihan; Amalia , Nurul (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Interest in learning is an important factor in students’ success in understanding subject matter, especially in mathematics which is often considered difficult and less interesting. Low interest in learning can have an impact on suboptimal learning outcomes. This study aims to analyse the effectiveness of game-based learning in increasing students’ interest in learning mathematics at MIN 36 Aceh Besar. The method used is Classroom Action Research (PTK) with two cycles, involving observation, interviews, questionnaires, and formative tests. The results showed that this method increased students’ engagement and motivation in learning. Students were more enthusiastic, active in discussions, and showed better concept understanding. In addition, game-based learning helps students develop critical thinking and problem-solving skills. However, challenges such as limited facilities, teacher readiness, and parental support are still obstacles in implementing this method. Therefore, supporting strategies are needed so that game-based learning can be optimally implemented. With proper planning, this method can be an effective strategy in increasing students‘ interest and understanding of mathematics, creating a more interactive learning environment, and improving students’ overall learning outcomes.